Evaluating the Long-Run Dynamics of Inflation, Unemployment, and Exchange Rates on Economic Growth: An Econometric Analysis of Time Series Data from Bangladesh with Verification of Okun’s Law - Islam, Md Aminul; Khatun, Amina; Haque, Md Obidul (South Asian Journal of Social Sciences and Humanities, 2025)
The foreign exchange rate, jobless rate, rate of inflation, and real GDP have always been considered to be the most burning issues for the world. This study seeks to analyze the effects of exchange rates, unemployment rates, and price levels on real GDP from 1991 to 2023, utilizing time series statistical methods. The research utilized sophisticated econometric techniques to analyze the findings. The series’ stationary properties were initially assessed using the Augmented Dickey-Fuller unit root test. The Johansen co-integration approach determines the variables’ long-term relationship. Granger casualty test was used to determine factor causal linkages. The empirical findings from the cointegration test indicate that, over the long term, both the exchange rate and the inflation rate exert a significant positive influence on the real gross domestic product (RGDP) in Bangladesh. On the contrary, the unemployment rate adversely affects real Gross Domestic Product (RGDP) in Bangladesh, this signifies that why Okun’s Law has the existence in Bangladesh. The findings from the vector error correction model (VECM) suggest that inflation and unemployment are expected to reach equilibrium following a period of error correction; however, the exchange rate and real GDP show minimal significant adjustment towards achieving long-run equilibrium. The results of the Granger test indicate a bilateral causal relationship between unemployment and the exchange rate. The findings derived from the impulse response function show that in a very few cases the external shocks have been neutralized for a certain period of time but in most cases the external shocks have not been neutralized.